Respon Pendidikan Dasar Terhadap Kebijakan Pembelajaran Jarak Jauh Selama Pandemi Covid-19 di Jawa Tengah - Sri Yunita Simanjuntak; Kismartini Kismartini (Peneliti.net, 2020)
One effort to prevent Covid-19 transmission to students is to issue a Distance Learning (PJJ) policy. The purpose of this study was to look at the response of the basic education unit to the implementation of PJJ policies, namely the level of school compliance implementing the policies, activities undertaken by teachers in PJJ, student responses, and parents' responses. The research method is descriptive with a qualitative approach. Data collection techniques in the form of questionnaires that are circulated online through Google form. Respondents in this study were principals, teachers, students and parents at the SD / MI and SMP / MTs levels in 5 Tanoto Foundation partner districts / cities in Central Java Province. Analysis of the data used is descriptive percentage using pivoting. Sample schools were 73 out of a total of 118 populations with a total of 1,023 respondents who were taken at random by simple random basis. The conclusion of this study is that 99.40% of schools have implemented PJJ policies; the most widely applied learning method by the teacher 42.86% is the reading method then summarizes the material; as much as 54.19% of students felt unhappy learning in PJJ because of several constraints such as lack of connection quality, limitations of communication devices and lack of understanding in the learning system provided; and 61.49% were satisfied because parents did not feel burdened in guiding children's learning and being closer to children.